The Aristocratic Discourse about the End of Tyranny in Athens and the Democratic Theory (De Rebus Antiquis, 2020)
In this paper classical Athenian discourses about the end of tyranny and the beginning of democracy are analyzed. In particular, taking as a starting point the perspective of some modern specialist about Athenian democracy as a political regime that lacked a theory or systematic thinking as sustenance, aristocratic elements present in democratic discourse are taken into account. Lastly, the discourses about the end of tyranny are situated in the broader context of ideological disputes about the political capability of the masses.
Keywords: Athens; Discourse; Democracy; Aristocracy; Democratic Theory